2019
DOI: 10.1021/acsaem.9b01520
|View full text |Cite
|
Sign up to set email alerts
|

Overcharge Investigations of LiCoO2/Graphite Lithium Ion Batteries with Different Electrolytes

Abstract: Although overcharging has been under extensive investigation for lithium ion batteries, the mechanism underneath still remains a “dark art” with little rational understanding. In this work, the degradation behaviors of LiCoO2/artificial graphite full cells using 1 M LiPF6 in ethylene carbonate (EC)/diethyl carbonate (DEC) electrolyte or 1 M LiPF6 in EC/dimethyl carbonate (DMC) electrolyte (both with a 3/7 weight ratio) after overcharge are investigated in detail for the first time. By the means of combining li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 55 publications
0
15
0
Order By: Relevance
“…The high terminal voltage at rupture possibly came from increase in cell internal resistance, which could originate from decomposition of electrode and electrolyte and separator shutdown. [ 18,30 ] It has been observed that LIBs overcharged at a 3 C rate had higher voltage at rupture compared with LIBs overcharged at 1 C rate. [ 39 ] The high overcharging rate can be the reason for the observed high voltage at rupture in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high terminal voltage at rupture possibly came from increase in cell internal resistance, which could originate from decomposition of electrode and electrolyte and separator shutdown. [ 18,30 ] It has been observed that LIBs overcharged at a 3 C rate had higher voltage at rupture compared with LIBs overcharged at 1 C rate. [ 39 ] The high overcharging rate can be the reason for the observed high voltage at rupture in this study.…”
Section: Resultsmentioning
confidence: 99%
“…To analyze the effect of charging rate on heat generation within the pouch cell, cell #1 was CC charged at 1 C rate up to 5.4 V. After reaching around 5.4 V, gas generation and electrode degradation in LIB became obvious. [ 11,30 ] Cell #1 was then CC charged at 5 C rate until explosion. Cell #2 was CC charged at 5 C rate constantly until cell explosion.…”
Section: Methodsmentioning
confidence: 99%
“…XPS measurements were conducted on a Thermo Fisher K -alpha (USA) XPS system to study CEI and SEI films . GC-MS measurements were adopted to analyze the electrolyte decomposition on a Thermo Scientific ISQ device . LC-QTOF-MS was performed on Xevo G2-XS QTOF (Waters Corporation, USA) to have a deeper investigation of the decomposition of the electrolyte qualitatively and quantitatively …”
Section: Methodsmentioning
confidence: 99%
“…The commercial electrolyte system usually comprises carbonate solvent and lithium salt, which undergoes reduction during the first charge–discharge cycle. As a result, SEI and CEI layers consisting of inorganic and organic decomposition compounds are formed. , In an ideal condition, the SEI and the CEI act as protective layers to prevent further electrolyte decomposition by the prohibition of the electron transport in the successive charge–discharge cycling . Through the surface films, lithium ions could intercalate into the electrode material without the structural changes of the host.…”
Section: Introductionmentioning
confidence: 99%
“…The higher device voltage increases the probability of over-oxidation on the fast-switching ECP component before the reaction of the ion-storage materials reaches equilibrium (MO x + y Li + + y e – = Li y MO x ). Additionally, high device voltage leads to problems including interfacial electrolyte decomposition . Therefore, to stabilize ECP-based hybrid electrochromic devices, a low device voltage is beneficial. , This requires the MCC transition-metal oxide material to exhibit excellent charge-balancing capability in an electroactive window that is closely matched with that of the ECPs.…”
Section: Introductionmentioning
confidence: 99%